Real-time monitoring and kinetic parameter estimation of the affinity interaction of jArtinM and rArtinM with peroxidase glycoprotein by the electrogravimetric technique - Pesquero, N. C. [UNESP]; Pedroso, M. M.; Watanabe, A. M. [UNESP]; Goldman, M. H. S.; Faria, R. C.; Roque-Barreira, M. C.; Bueno, Paulo Roberto [UNESP] (Elsevier Advanced Technology, 2010)
ArtinM is a D-mannose binding lectin that has been arousing increasing interest because of its biomedical properties, especially those involving the stimulation of Th1 immune response, which confers protection against intracellular pathogens The potential pharmaceutical applications of ArtinM have motivated the production of its recombinant form (rArtinM) so that it is important to compare the sugar-binding properties of jArtinM and rArtinM in order to take better advantage of the potential applications of the recombinant lectin.In this work, a biosensor framework based on a Quartz Crystal Microbalance was established with the purpose of making a comparative study of the activity of native and recombinant ArtinM protein The QCM transducer was strategically functionalized to use a simple model of protein binding kinetics. This approach allowed for the determination of the binding/dissociation kinetics rate and affinity equilibrium constant of both forms of ArtinM with horseradish peroxidase glycoprotein (HRP), a N-glycosylated protein that contains the trimannoside Man alpha 1-3[Man alpha 1-6]Man, which is a known ligand for jArtinM (Jeyaprakash et al, 2004). Monitoring of the real-time binding of rArtinM shows that it was able to bind HRP, leading to an analytical curve similar to that of jArtinM, with statistically equivalent kinetic rates and affinity equilibrium constants for both forms of ArtinM The lower reactivity of rArtinM with HRP than jArtinM was considered to be due to a difference in the number of Carbohydrate Recognition Domains (CRDs) per molecule of each lectin form rather than to a difference in the energy of binding per CRD of each lectin form. (C) 2010 Elsevier B V. All rights reserved
Keywords: Artocarpus integrifolia; ArtinM; Affinity equilibrium constant; Recombinant protein; Quartz Crystal Microbalance; Lectin